(untitled) (Research, Society and Development, 2023)
To analyze and describe the viscosity and the stress in relation to the shear rate of eleven facial fillers of four commercial HA brands with authorized use in Brazil through the flow sweep rheological analysis method. The rheological parameter of viscosity (η) was analyzed by rheometry tests through flow sweep. The behavior of shear stress showed that Rennova Fill Lido® and Lift Lido® have higher viscosity ratios (ƞ = 336 Pa.s and ƞ = 406 Pa.s, respectively). In contrast, Hialurox® brand fillers showed the lowest viscosity value (ƞ) (Hialurox Ultra Soft 8 mg/g® ƞ= 9 Pa.s, Fine 16 mg/g ƞ= 29 Pa.s, Fill 24 mg/g ƞ= 36 Pa.s, Lift 26 mg/g ƞ= 50 Pa.s). The flow sweep showed variations in the viscosity (ƞ) of the eleven HA dermal fillers. Rennova Fill Lido® and Lift Lido® have a lower degree of spreadability and are less susceptible to shear forces and yield strength, making them ideal candidates for the intended treatment.